TEKNIK HIPNOTERAPI DALAM KONSELING ISLAMI - Lisa Rahmania; Fitri Nurhaliza Ridwan; Nurul Azmi (STAI Pelabuhan Ratu, 2025)
Hypnotherapy is a psychological technique used to help individuals overcome psychological and physical problems through hypnosis. This article aims to explain the basic concept of hypnotherapy, its history of development, stages of implementation, and the benefits and risks of its application in the context of Islamic counseling. The method used in this writing is a literature study with a qualitative approach. The results of the study indicate that hypnotherapy has benefits in increasing concentration, reducing stress, and encouraging more positive behavioral changes, especially in the fields of education and spiritual development. However, there are psychological risks and abuse if carried out by incompetent parties. Therefore, the implementation of hypnotherapy must follow ethical principles and be carried out by professional practitioners. The implications of the results of this study indicate that hypnotherapy can be a relevant alternative technique for use in holistic and value-based Islamic counseling practices.